Neural Correlates of Learning to Attend - Kelley, Todd A.; Yantis, Steven (Frontiers in Human Neuroscience, 2010)
Recent work has shown that training can improve attentional focus. Little is known, however, about how training in attention and multitasking affects the brain. We used functional magnetic resonance imaging (fMRI) to measure changes in cortical responses to distracting stimuli during training on a visual categorization task. Training led to a reduction in behavioural distraction effects, and these improvements in performance generalized to untrained conditions. Although large regions of early visual and posterior parietal cortices responded to the presence of distractors, these regions did not exhibit significant changes in their response following training. In contrast, middle frontal gyrus did exhibit decreased distractor-related responses with practice, showing the same trend as behaviour for previously observed distractor locations. However, the neural response in this region diverged from behaviour for novel distractor locations, showing greater activity. We conclude that training did not change the robustness of the initial sensory response, but led to increased efficiency in late-stage filtering in the trained conditions.